Electrochemical performance of solid oxide fuel cells with Sm, Nd co-doped Ce0.85(SmxNd1−x)0.15O2−δ electrolyte. Issue 5 (June 2015) - Ma, Lei; Zhao, Kai; Kim, Bok-Hee; Li, Qian; Huang, Jinliang
Abstract: To investigate the application potential of Ce0.85 (Sm x Nd1− x )0.15 O2− δ (SNDC) ( x =0.0, 0.2, 0.4, 0.6, 0.8, 1.0) as electrolytes for Intermediate-Temperature Solid Oxide Fuel Cells (IT-SOFC), single cells with identical electrode structures but using different electrolytes were fabricated. Their performance was investigated under identical conditions. It was found that the single cell with the SNDC ( x =0.6) electrolyte had both the highest Open Circuit Voltage (OCV) and maximum power density (MPD) of 0.87 V and 715 mW cm −2 at 600 °C, respectively. This can be mainly attributed to the largest transference number of oxygen ions and the highest conductivity of the SNDC ( x =0.6). An anode functional layer (AFL) was applied to another single cell, which used SNDC ( x =0.6) as its electrolyte. Subsequently, a significant improvement in the performance (the MPD at 600 °C was 980 mW cm −2 ) was achieved.